Finite element analysis of stress in mandibular molars repaired after fractured instrument removal - Salih Düzgün; Emir Esim; Tuğrul Aslan; Ayşe Tuğba Eminsoy Avcı (BMC Oral Health)
Abstract Background This study assessed stress distributions in simulated mandibular molars filled with various materials after the removal of fractured instruments from the apical thirds of the root canals. Methods Finite element models of the mesial and distal root canals were created, where fractured instruments were assumed to be removed using a staging platform established with a modified Gates-Glidden bur (Woodpecker, Guangxi, P.R. China). Each canal was treated with different materials: Biodentine (Septodont, Saint Maur-des-Fosses, France), mineral trioxide aggregate (MTA), and gutta-percha. In addition to these, four control models were also created. In total, 14 models were generated and subjected to a 300 N force applied at a 45° angle to simulate the stress. Results Model 1 (Biodentine) and 2 (Gutta-percha + Biodentine) showed the lowest stresses among mesial root canal models, whereas Model 5 (Gutta-percha) showed the highest. Among distal root canal models, Model 6 (Biodentine) and 7 (Gutta-percha + Biodentine) showed the lowest stresses, while Model 10 (Gutta-percha) showed the highest. In addition, Biodentine (Septodont) and Gutta-percha + Biodentine (Septodont) produced similar stress levels in both mesial and distal roots, while MTA and Gutta-percha + MTA led to increased stresses, especially in the distal root. Among the control models, the highest maximum von Mises stress values were in Model 13 and Model 14, which had a staging platform and were not filled with any root canal filling material, after the broken instrument was removed. Conclusions Biodentine (Septodont) may be preferable to MTA for filling staging platform cavities post-fractured instrument removal due to lower stress levels. Furthermore, calcium silicate-based materials alone or in combination with Gutta-percha showed similar stress levels, suggesting their potential use for root canal filling. All models demonstrated structural integrity within safe limits.